2019
DOI: 10.5958/0974-0279.2019.00009.0
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and reduction in input costs in agriculture: case of genetically modified cotton

Abstract: Adoption of labour-saving agricultural technologies is often determined by peak-season labour scarcity and uncertainty in labour supply, besides the need to reduce overall cost of production. Adoption of labour-saving technological innovations could also be justified on efficiency grounds. Technology-led agricultural growth is believed to ensure economic gains to cultivators, increase in real wages and creation of employment opportunities. This paper estimates changes in mean technical efficiency in herbicidet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This raises the idea that various forms of protectionism are preferred in less developed economic sectors; thus, more developed economies should place their emphasis on liberal free trade and market relations in order to facilitate growth and efficiency. Mehta [28] focused on the effect the technical efficiency had on the labor market, stressing its impact on lowering demand for labor in agriculture, but also showing its negative consequences during peak moments. Siddique et al [29] showed a strong correlation between the education level of farmers and the technical efficiency level.…”
Section: Factors Influencing Agricultural Performancementioning
confidence: 99%
“…This raises the idea that various forms of protectionism are preferred in less developed economic sectors; thus, more developed economies should place their emphasis on liberal free trade and market relations in order to facilitate growth and efficiency. Mehta [28] focused on the effect the technical efficiency had on the labor market, stressing its impact on lowering demand for labor in agriculture, but also showing its negative consequences during peak moments. Siddique et al [29] showed a strong correlation between the education level of farmers and the technical efficiency level.…”
Section: Factors Influencing Agricultural Performancementioning
confidence: 99%